Writing Development Through Materials That Focus on Peer Feedback in an EFL Context (2020)
This paper reports on the findings of a research project carried out in order to analyze how English as a foreign language writing evolves when eighth graders from José Max León School are engaged in developing worksheets that focus on peer feedback. This study emerged from my concern that most of my eighth-grade students did not consider my feedback during the writing process. To collect and manage the data of this action research study, I used the qualitative approach and three instruments: field notes, students’ artifacts, and a survey. The results presented a significant improvement in the students’ writing skills thanks to the implementation of peer feedback. Additionally, the worksheets implemented were relevant for students since they were based on appealing content, which contributed to enhancing their engagement and feedback participation.